2019
DOI: 10.1136/thoraxjnl-2019-213744
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint impact of the choice of inhalers for asthma and COPD

Abstract: In the 1990s, metered dose inhalers (MDIs) containing chlorofluorocarbons were replaced with dry-powder inhalers (DPIs) and MDIs containing hydrofluorocarbons (HFCs). While HFCs are not ozone depleting, they are potent greenhouse gases. Annual carbon footprint (CO2e), per patient were 17 kg for Relvar-Ellipta/Ventolin-Accuhaler; and 439 kg for Seretide-Evohaler/Ventolin-Evohaler. In 2017, 70% of all inhalers sold in England were MDI, versus 13% in Sweden. Applying the Swedish DPI and MDI distribution to Englan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 3 publications
7
139
0
12
Order By: Relevance
“…Switching to dry powder inhalers can save drug related greenhouse gas emissions and financial costs simultaneously 18. In 2017, 70% of all inhalers sold in England were metered dose inhalers compared with 13% in Sweden, where there has been a more rapid transition to dry powder inhalers 19. Guidance from the National Institute for Health and Care Excellence (NICE) in England has already stated that both patient and population health need to be considered when prescribing inhalers 20…”
Section: Reducing Avoidable Emissions and Ecological Damagementioning
confidence: 99%
“…Switching to dry powder inhalers can save drug related greenhouse gas emissions and financial costs simultaneously 18. In 2017, 70% of all inhalers sold in England were metered dose inhalers compared with 13% in Sweden, where there has been a more rapid transition to dry powder inhalers 19. Guidance from the National Institute for Health and Care Excellence (NICE) in England has already stated that both patient and population health need to be considered when prescribing inhalers 20…”
Section: Reducing Avoidable Emissions and Ecological Damagementioning
confidence: 99%
“…22 It was calculated that if England applied the Swedish distribution of pMDIs and DPIs, 550 kt of CO 2 would be saved annually-which corresponds to approximately 2.6% of NHS England's total carbon footprint. 22 Furthermore, the inappropriate disposal of pMDIs contributes further to their environmental impact. 23 Although some pMDIs do have dose counter mechanisms, this is not universal (in contrast to DPIs) and means that patients may not know how many doses are left in their inhalers.…”
Section: Environmental Impac Tmentioning
confidence: 99%
“…In fact, it has been widely reported that the proportion of patients using the correct technique with pMDIs without a spacer is low. Two separate studies reported correct technique using a pMDI as compared with DPIs to be 23%‐43% and 53%‐59% respectively 18,22 . Effective use of a DPI requires the patient to generate a peak inspiratory flow (PIF) that overcomes the internal resistance of the inhaler.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“… 1 The ELLIPTA DPI device, compared with MDIs, has been associated with shorter training times, fewer errors in use, less requirement for coordination, environmental benefits and greater patient preference, with implications for adherence and potentially treatment outcomes. 2 , 3 The ELLIPTA DPI has also been shown to be easy to use with few errors in use across different age groups in patients with COPD. 4 In order to use DPIs adequately, patients must generate a level of inspiratory effort based on the internal resistance of the inhaler, and thereby provide energy for dose emission and de-aggregation of the inhalation powder to generate particles of a suitable size for deposition within the lower respiratory tract.…”
Section: Introductionmentioning
confidence: 99%